Exploring the perspectives of members of international tuberculosis control and research networks on the impact of COVID-19 on tuberculosis services: a cross sectional survey - Oluwatosin Nkereuwem; Esin Nkereuwem; Arnauld Fiogbe; Eno E. Usoroh; Abdou K. Sillah; Olumuyiwa Owolabi; Marc Tebruegge; Abdoulie Badjan; Beate Kampmann; Toyin Togun (BMC, 2021)
Abstract Background The COVID-19 pandemic has caused major disruption to healthcare services globally and has impacted on tuberculosis (TB) patients and TB diagnosis and treatment services both in low- and high-income countries. We therefore explored the perspectives of members of regional and international TB control and research networks to further understand TB service disruptions and compared the experiences of members from West African and European countries. Methods This cross-sectional, explorative descriptive study was conducted from May to July 2020 using an open online survey with target respondents from both West African and European countries. The survey comprised discrete questions exploring challenges faced with TB screening, diagnosis, treatment, prevention, and changes implemented. Additionally, respondents were asked to provide recommendations for remedial actions. Results We analysed responses from 124 respondents based in 29 countries located in Europe and West Africa. About half of the respondents reported challenges in delivering routine TB services during the COVID-19 pandemic, with over one third reporting having some form of guidance issued regarding maintaining delivery of routine TB services. Respondents emphasised the need for strengthening TB services especially in light of COVID-19 pandemic. Considerable similarities were found between the challenges experienced by TB professionals in both West African and European settings. Responses also highlighted the hidden challenges faced in some countries prior to the COVID-19 pandemic, especially in some West African settings where staff shortages and laboratory issues predated COVID-19. Conclusions TB control and research professionals in West African and European settings experienced similar challenges to the delivery of TB diagnosis and treatment services due to the COVID-19 pandemic, and highlighted the need for clear communication of guidelines, prioritisation of routine TB service delivery, ongoing health education, and possible integration of TB and COVID-19 services to ensure that TB services are more resilient against the impact of the pandemic.